2005
DOI: 10.1152/ajpgi.00491.2004
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent networks of submucous neurons controlling intestinal secretion: a modeling study

Abstract: Secretomotor neurons, immunoreactive for vasoactive intestinal peptide (VIP), are important in controlling chloride secretion in the small intestine. These neurons form functional synapses with other submucosal VIP neurons and transmit via slow excitatory postsynaptic potentials (EPSPs). Thus they form a recurrent network with positive feedback. Intrinsic sensory neurons within the submucosa are also likely to form recurrent networks with positive feedback, provide substantial output to VIP neurons, and receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…The finding that nicotinic receptors are not required for the induction of CT-evoked secretion is also compatible with our modelling study (9). In our model, hyperactivity in the recurrent networks is enhanced by fast synaptic transmission of the type mediated by nicotinic receptors but is not dependent on it.…”
Section: Ct Effects On Basal Secretionsupporting
confidence: 91%
See 2 more Smart Citations
“…The finding that nicotinic receptors are not required for the induction of CT-evoked secretion is also compatible with our modelling study (9). In our model, hyperactivity in the recurrent networks is enhanced by fast synaptic transmission of the type mediated by nicotinic receptors but is not dependent on it.…”
Section: Ct Effects On Basal Secretionsupporting
confidence: 91%
“…We (9) have recently reported that an anatomically realistic model of the submucous plexus can account for such a divergence in mechanism. This model predicts that the induction of hypersecretion depends on positive feedback within recurrent excitatory networks of VIP neurons and the intrinsic sensory neurons of the submucosa.…”
Section: Ct Effects On Basal Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that a combination of NK 1 receptor and nicotinic input is required for the circuit to activate rapidly and that blockade of either component will prolong the time taken to activate the circuit and reduce final firing rate. A pattern of this type was described in previous modeling work on the submucous plexus (9). Serosal lidocaine might, in that case, affect both components.…”
Section: Discussionmentioning
confidence: 55%
“…Nurgali et al (43) have shown that in mouse distal colon, neurons with Dogiel type II morphology often do not exhibit a pronounced after-hyperpolarizing potential (AHP). Interestingly, in recent modeling studies (9, 59), we have shown that suppression of the AHP and/or increased synaptic efficacy in submucous sensory networks will lead to enhanced responses of VIP secretomotor neurons to sensory stimulation (9). Thus a potential explanation for the increased response in mice could be due to a reduced AHP in AH neurons, rendering them more sensitive to, for instance, mechanical stimuli.…”
Section: Discussionmentioning
confidence: 83%